The order of immunoglobulin light chain κ and λ usage in primary and secondary lymphoid tissues of germ-free and conventional piglets - Stepanova, Katerina; Sinkorova, Jana; Srutkova, Dagmar; Sinkora, Marek; Sinkora, Simon; Splichal, Igor; Splichalova, Alla; Butler, John E; Sinkora, Marek (Developmental and comparative immunology, 2022)
In pigs (Sus scrofa), the initial immunoglobulin rearrangement of the κ light chain is replaced by λ before the heavy chains rearrange, and the light chains may rearrange even later. This study investigates whether these developmental differences are reflected in the usage of IGK and IGL genes. We found large differences between peripheral B cells and those developing in the bone marrow, and between B cells in germ-free piglets and conventional pigs. During early B cell development in the bone marrow, more 3' V and 5' J gene segments for both light chains are used. However, in the peripheral naive repertoire, more 5' IGLV and 3' IGLJ genes are used. A similar shift toward the use of more 5' IGKV and 3' IGKJ genes is observed later after antigen exposure in conventional pigs. The expression profile showed that most λ+ B cells are generated earlier, while κ+ B cells develop from late precursors that already contain the λ rearrangement. The initial λ rearrangement is retained in both λ+ and κ+ B lymphocytes, and multiple λ transcripts can be found in individual cells. The overall pool of the IGLV repertoire is therefore much larger and more diversified than for IGKV. The κ repertoire is further restricted to the preferential use of only two major IGKV genes, reflecting the limitation for only two consecutive rearrangements. Tracing of silenced λ transcripts in κ+ B cells further confirmed the unconventional mechanism of differential rearrangements in pigs. Our results underline the diversity of the immune system among mammals.
Keywords: lymfoidní tkáň; Immunoglobulin light chains; Genes, Immunoglobulin; Immunoglobulin Light Chains; Immunoglobulin rearrangement; B cell development; Lymphoid Tissue; Animals; lehké řetězce imunoglobulinů; imunoglobuliny - lambda-řetězce; B cell receptors; B-lymfocyty; geny pro imunoglobuliny; Immunoglobulin kappa-Chains; Swine; zvířata; imunoglobuliny - kappa-řetězce; B-Lymphocytes; prasata; Porcine immune system; savci; Lymphocyte differentiation; Immunoglobulin lambda-Chains; Mammals